Uma análise crítica da BNCC na área de Língua Portuguesa a partir das contribuições de Freire - Fraga, Lídice Tiede (Universidade Federal de São Carlos, 2020)
ABSTRACT FRAGA, Lídice Tiede. A Critical Analysis of the BNCC in the Portuguese Language Area from the Contributions of Freire. 2020. 89 p. (Master´s Degree in Education) - Universidade Federal de São Carlos [Federal University of São Carlos], Sorocaba campus, Sorocaba/SP, 2020. The objective of this research was to seek to understand the Base Nacional Comum Curricular (BNCC) [National Common Curricular Base] of the Portuguese Language for the final years of Elementary School, through the comparison between the general intentions of the BNCC and the specific area, using the categories of Bakhtinian and Freirean analysis: dialogism and dialogicity, and their conceptual and meaning unfolding. The objective of this work was also to investigate to what extent this document, which guides the construction of federal, state and municipal curricular, presents a theoretical-methodological discourse consistent with the contextualized concept of teaching for the adoption of a critical-dialogical pedagogical reference, committed to the construction of knowledge based on the reality of students and the voices of communities. Thus, through a qualitative approach, the analysis of the document was based on the theoretical-methodological framework of historical-dialectic materialism and Dialogical Discourse Analysis (DDA). In order to carry out the analysis, a theoretical construction was made about the history of national curriculum policies, critical and non-critical curricular conceptions, specific curriculum history of Portuguese language and explanation of the assumptions of Bakhtinians and Freireans, markers of the analytical categories listed. Still with regard to the realization of the analysis, the discourses of parts of the BNCC - general and specific part - on which the categories focused, were confronted in order to verify the enunciative coherence and whether, effectively, the basis is committed to its own educational project, based on ethical, political and aesthetic principles, of building a just society through a process of teaching and learning contextualized and dialogical. Within this perspective, this work has evidenced an internal discursive incoherence regarding the categories with radical -dialog.
A critical analysis of the BNCC in the Portuguese Language area from the contributions of Freire
Keywords: Currículo; Dialogismo; Dialogicidade; Bakhtin; Freire; BNCC; Curriculum; Dialogism; Dialogicity; Critical curriculum; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUA PORTUGUESA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES